Metal Box / A History - Reader W. J; Slinn Judy (Heinemann, 1976)
Foreword, Illustrations, Tables, The Expanding Market in Late Victorian England, The Ancestors: Victorian Tin-Box Makers, Decorated Tins, Cutter- Lids for Cigarettes, The Tin-Box and Canister Trade Before 1914, Coming Together 1914-1929: The Formation of Metal Box and Printing Industries Limited, The American Invasion 1929-1931, Metal Box: Barlow's Revolution 1929-1935, Netal Box at Home 1930-1939, Expansion in Depression, Rationalization in Tins, The Firm and the Industry 1939, Overseas Foundations 1930-1939, Wartime, The Post-War Market at Home, The American Connection after 1945, Life at Court: Problems of Management 1943-1954, The Long Boom: World Markets 1945-1970, Commonwealth Companies, Europe, The Overseas Experience 1945-1970, Metal Box Examined: the Monopolies Commission and the Business in 1970, Appendices, Index.